O primeiro templo de Jerusalém segundo o imaginário pós-exílico: um estudo de sua relevância, função social e seus aspectos - Montalvão, Sérgio Aguiar (2015)
This doctoral thesis aims to present what came to be built through the Solomon s First Temple Imaginary, which many people still believe in the nowadays that it is factual. However, the Temple as presented in the Hebrew Bible never existed, because no more than an annex king s palace; it s also not factual the myths circulating the kings David and Solomon, which were not as grand as the Hebrew Bible points. Nevertheless, on two occasions in the history of Judah, the Deuteronomist Revolution and the Return of the Captivity, the Temple had a centralizating function and required many founding myths to legitimize it. With such myths, the people who were near the Temple felt more part of the House of Yahweh for believing participate of a plan established by the Creator of the Universe and all the stories invented and developed by the Deuteronomist and the Priestly gave them greatest joy and hope. What happened in fact was the king s power legitimacy in the context of Deuteronomist Reform and the priest s power in the return of the Captivity in the early Persian period. As for the post-exile, for being a more recent period, is greater amount of elements that characterize the stimulation of popular imaginary regarding the First Temple than in the period of the Deuteronomist Reform, despite the latter being period of prosperity for the Kingdom of Judah